Analytic continuation of dimensions in supersymmetric localization - Anastasios Gorantis; Joseph A. Minahan; Usman Naseer (Journal of High Energy Physics, 2018)
Abstract We compute the perturbative partition functions for gauge theories with eight supersymmetries on spheres of dimension d ≤ 5, proving a conjecture by the second author. We apply similar methods to gauge theories with four supersymmetries on spheres with d ≤ 3. The results are valid for non-integer d as well. We further propose an analytic continuation from d = 3 to d = 4 that gives the perturbative partition function for an N $$ \mathcal{N} $$ =1 gauge theory. The results are consistent with the free multiplets and the one-loop β-functions for general N $$ \mathcal{N} $$ = 1 gauge theories. We also consider the analytic continuation of an N $$ \mathcal{N} $$ = 1 preserving mass deformation of the maximally supersymmetric gauge theory and compare to recent holographic results for N $$ \mathcal{N} $$ = 1∗ super Yang-Mills. We find that the general structure for the real part of the free energy coming from the analytic continuation is consistent with the holographic results.